Subsurface oxygen minima regulated by remineralization and bottom flushing along 123°E in the inner East China Sea - Wang, Bin; Chen, Jianfang; Jin, Haiyan; Li, Dewang; Gao, Shengquan; Tian, Shichao; Sun, Lin; Zhang, Haizhou; Li, Linwei (Frontiers in Marine Science, 2023)
The summer hypoxia off the Changjiang Estuary is one of the largest coastal hypoxic systems in the world and displays the spatial heterogeneity in recent years. Based on observation data in the summer of 2014, the hypoxia was identified both in the bottom and mid-layer. Except for the typical bottom hypoxia in the submarine canyon, the subsurface oxygen minima (SOM) was captured in the mid-layer of 10 15m with the lower dissolved oxygen in mid-layer than at the bottom (30-50 m). This SOM phenomenon was located in the lower boundary of the pycnocline and above the Taiwan Warm Current (TWC) and Kuroshio Subsurface Water (KSSW). Due to the southern expansion of Changjiang Diluted Water (CDW), high phytoplankton biomass (the maximum chlorophyll a of 25 μg/L, pH of 8.6 and DO of 11mg/L) band occupied the surface area along 123°E. By analyzing the 24-hours continuous observation and high-resolution profile data, we revealed that the subsurface oxygen minima were predominantly controlled by in-situ remineralization and bottom flushing effects. Fast local consumption occurred near the stable pycnocline, while the lateral transport of oxygen-rich ambient water replenishes the bottom oxygen deficit. We summary and contextualize three hot spots of hypoxia into a conceptual diagram and emphasis the influences of advection, mixing and respirations on their location and severity. Overall, compared with the previous discussion about low DO background of TWC/KSSW, this research highlights the flushing effects of TWC/KSSW that will reshape the hypoxia structure and alleviate the hypoxia severity in the south hypoxia area off the Changjiang Estuary.